Factors influencing implementation of aerobic exercise after stroke: a systematic review. Issue 17 (14th August 2021) - Gaskins, Nicola J.; Bray, Emma; Hill, James E.; Doherty, Patrick J.; Harrison, Alexander; Connell, Louise A.
Abstract: Objectives: This systematic review aimed to explore the perspectives of healthcare, exercise, and fitness professionals working with people post-stroke regarding the factors affecting the implementation of aerobic exercise after stroke. Data Sources: OVID SP MEDLINE, OVID SP EMBASE, and CINAHL were searched from inception to December 2018 using a combination of search terms with synonyms of stroke, aerobic exercise and barriers/facilitators. Review methods: Studies focusing on the factors affecting implementation of aerobic exercise after stroke from staff perspectives were included with no restriction on the types of study design. For inclusivity, a broad definition of aerobic exercise was used. Review authors independently extracted data from included studies using domains from the Consolidated Framework for Implementation Research, then synthesised using a framework synthesis approach. Retrospective automated screening was conducted using Rayyan software. Results: Twenty studies were included. Four reported on implementation of aerobic exercise, sixteen on general exercise interventions, all post-stroke. Factors identified as influencing implementation of aerobic exercise after stroke included professionals' self-efficacy and knowledge about stroke, patients' needs, communication and collaboration within and between organisations and resources such as equipment, staff and training. Conclusions: Key factors influencing the implementation of aerobic exercise after stroke included characteristics of the staff and intervention and system-level issues, some of which are modifiable. Further research should evaluate strategies which specifically target these modifiable factors to facilitate implementation in practice. IMPLICATIONS FOR REHABILITATION: Aerobic exercise after stroke is an effective intervention but there are challenges to implementation from a staff and system perspective. Any changes to the identified factors should be tailored to suit the staff group and setting. Provision of training and knowledge-sharing could improve staff's confidence in the prescription and delivery of aerobic exercise after stroke though other implementation strategies should also be considered.